Investigation on micronized biomass silica as a sustainable material. (July 2015) - Prameetthaa, J.; Bharatkumar, B.H.; Iyer, Nagesh R.
Abstract: Micronized biomass silica (MBS) is an agricultural waste obtained from controlled burning of rice husk and grind in jar mill. This paper investigates the optimum percentage of MBS for the replacement of cement by conducting several experiments with the blended cement paste and mortar with MBS percentages varying from 0, 4, 8 and 12. In addition, hydration products were also investigated in the blended cement paste through X-ray diffraction. Due to the pozzolanic reaction of MBS with cement hydrates, secondary calcium silicate hydrates (CSH) were formed and also MBS which has a potential to reduce the intensity of Ca(OH)2 exhibited improved properties. The experimental results showed that the optimum percentage of MBS for the replacement of cement was 8% for the materials used in this study. The mechanical and durability properties of recycled aggregate concrete by replacing cement with 8% MBS were also carried out and it was found that the concrete exhibited improved properties. There by, using MBS one can overcome the drawbacks of recycled aggregate concrete as it acts as a supplementary cementitious material. Thus, by combining recycled concrete aggregate with MBS will achieve sustainable development.